Design of a 2D Animated Media for Youth: “Sweet Smoke, Hidden Poison in Fragrant Vapor.” - คำสิงห์ สหรัฐ; ขำเนตร ศุภเกียรติ; เสมอวงษ์ ศรีสุภัค; ดีเจริญชิตพงศ์ จิรวิญญ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The research entitled “The Development of a 2D Animation Media ‘Sweet Smoke Hidden Poison in Fragrant Vapor’ employed a Research and Development (R&D) approach. The objectives of this study were: 1) to study the process of designing and producing a 2D animation media entitled “Sweet Smoke Hidden Poison in Fragrant Vapor”; 2) to investigate the causes and factors influencing youths to use electronic cigarettes; 3) to analyze the effects of electronic cigarettes on physical health and adolescent development; 4) to promote knowledge, understanding, and appropriate attitudes regarding the harmful effects of electronic cigarettes; and 5) to encourage awareness in order to reduce risky behaviors related to e-cigarette use among youths. The research findings revealed that: 1) the evaluation of content quality by content experts showed an overall mean score of 4.59 with a standard deviation (S.D. = 0.17), which was interpreted at a very good level according to the evaluation criteria; 2) the evaluation of media quality by media experts indicated an overall mean score of 4.13 with a standard deviation (S.D. = 0.74), which was interpreted at a good level according to the evaluation criteria; and 3) the satisfaction assessment of 80 participants who were interested in the harmful effects of electronic cigarettes showed an overall mean score of 4.55 with a standard deviation (S.D. = 0.52), which was interpreted at the Excellent according to the evaluation criteria. These results indicate that the 2D animation media entitled “Sweet Smoke Hidden Poison in Fragrant Vapor” is of high quality and can be effectively used as an educational media to disseminate knowledge about the dangers of electronic cigarettes and to raise awareness among youths and the general public.